A Review of Cognitive UAVs: AI-Driven Situation Awareness for Enhanced Operations - Dehghan, Motahareh; Khosravian, Erfan (AI and Tech in Behavioral and Social Sciences, 2024)
The integration of artificial intelligence (AI) into unmanned aerial vehicles (UAVs) has significantly advanced the capabilities of these aerial platforms, particularly in enhancing situation awareness. This paper presents a comprehensive survey and review of AI-driven techniques to improve situation awareness for UAVs. We begin by defining situation awareness and its essential components—perception, comprehension, and projection—within the context of UAV operations. We then explore various AI methodologies, including machine learning, deep learning, computer vision, natural language processing, and data fusion, employed to augment UAVs’ abilities to perceive and interpret their environment. The paper examines diverse AI-enhanced UAV situation awareness applications across military, civilian, and commercial domains. Critical applications include advanced surveillance, target acquisition, search and rescue missions, environmental monitoring, traffic and crowd monitoring, infrastructure inspection, and delivery services. We also discuss the technical and operational challenges of implementing AI in UAVs, such as data quality, real-time processing, environmental impacts, and scalability. Ethical and legal considerations are also addressed, including privacy concerns and regulatory issues. In addition to a thorough review of current literature, we provide detailed case studies highlighting successful AI implementations in UAVs, offering practical insights and lessons learned. We identify emerging technologies and future research opportunities that have the potential to advance the field further, such as innovations in sensor technology and AI algorithms. Our findings underscore the transformative potential of AI in enhancing the situational awareness of UAVs, paving the way for more intelligent, autonomous, and effective aerial systems. This survey is a valuable resource for researchers, practitioners, and policymakers interested in understanding and leveraging the intersection of AI and UAV technology for various applications.